Nutritional Screening of Pulmonology Department Inpatients - Isabel Maia (2014)
Undernutrition is associated with worse clinical outcomes and so screening is recommended. Given the paucity of information on nutritional status and on the clinical impact of undernutrition in Pulmonology patients who have been hospitalized, it is of the utmost importance that it is studied. Through a longitudinal study conducted of 323 patients consecutively admitted to a Pulmonology hospital department, undernutrition was screened using the Malnutrition Universal Screening Tool and the association between length of hospital stay, pathology type, discharge destination and undernutrition risk was quantified. There was found to be a high proportion of patients at risk of undernutrition, with 18.3% at high risk and 15.5% at moderate risk. Patients at risk of undernutrition had a higher risk of dying during hospitalization (OR = 2.72, 95% CI: 1.48- 4.97). One in three patients admitted to this unit is at risk of undernutrition; chronic obstructive pulmonary disease was the pathology most strongly associated with undernutrition risk. Present data reinforces the need for screening for undernutrition on admission.